2021
DOI: 10.1029/2021je006897
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Rock Exhumation at the Rims of Kilometer‐Scale Lunar Craters

Abstract: Recent work using S-band (12.6 cm, 2,380 MHz) radar data from the LRO Miniature Radio-Frequency (Mini-RF) instrument revealed that while surface and subsurface rock populations associated with lunar impact ejecta are diminished with time due to space weathering processes, the rock content of impact crater interiors increases for the first ∼0.5 Gyr of a crater's lifetime (Fassett, Minton, et al., 2018). A separate study used thermal infrared measurements from the LRO Diviner thermal radiometer to infer that bou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
(94 reference statements)
1
16
0
Order By: Relevance
“…Several of the instruments on the Lunar Reconnaissance Orbiter (LRO) have provided new data relevant to rock populations and regolith evolution, particularly the Lunar Reconnaissance Orbiter Camera (LROC; Robinson et al., 2010), the Diviner Lunar Radiometer Experiment (Hayne et al., 2017; Paige et al., 2010), and Miniature Radio Frequency (Mini‐RF) radar (e.g., Cahill et al., 2014; Nozette et al., 2010; Raney et al., 2011). Many analyses of these data have focused on the rock abundance in craters' ejecta (Ghent et al., 2014; Fassett et al., 2018; Mazrouei et al., 2019; Nypaver et al., 2021), rather than in the intercrater regions of the maria. Additionally, the abundance of meter‐scale rocks has also been manually assessed with LROC in a few selected areas of particular interest, such as landing sites (Li et al., 2017; Watkins et al., 2019; Wu et al., 2018), as well as on a more global basis with machine learning (Bickel et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several of the instruments on the Lunar Reconnaissance Orbiter (LRO) have provided new data relevant to rock populations and regolith evolution, particularly the Lunar Reconnaissance Orbiter Camera (LROC; Robinson et al., 2010), the Diviner Lunar Radiometer Experiment (Hayne et al., 2017; Paige et al., 2010), and Miniature Radio Frequency (Mini‐RF) radar (e.g., Cahill et al., 2014; Nozette et al., 2010; Raney et al., 2011). Many analyses of these data have focused on the rock abundance in craters' ejecta (Ghent et al., 2014; Fassett et al., 2018; Mazrouei et al., 2019; Nypaver et al., 2021), rather than in the intercrater regions of the maria. Additionally, the abundance of meter‐scale rocks has also been manually assessed with LROC in a few selected areas of particular interest, such as landing sites (Li et al., 2017; Watkins et al., 2019; Wu et al., 2018), as well as on a more global basis with machine learning (Bickel et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such a scenario is predicted for rocky areas, where a range of rock sizes are expected (Bandfield et al 2011;Hayne et al 2017). This is supported by the finding that CPR values remain high in crater ejecta blankets for >3 Ga, which suggests that radardetectable (i.e., >∼10 cm) rocks persist in the near-subsurface even if the surface appears relatively rock-free in Diviner RA measurements (Ghent et al 2016;Nypaver et al 2021).…”
Section: Interpretation Of Ra H-parameter and Cprmentioning
confidence: 61%
“…Conversely, a signal interacting with a rough or rocky region of the lunar surface will experience multiple scattering events, meaning more signal will be returned with the same-sense polarization and CPR will be closer to or greater than 1. A number of studies have used CPR to investigate surface and subsurface physical properties on the Moon (e.g., Carter et al 2009;Campbell 2012;Cahill et al 2014;Ghent et al 2016;Nypaver et al 2021), finding that rocky surfaces such as impact crater ejecta blankets and impact melt deposits have high CPR and that rock-poor surfaces such as pyroclastic deposits display low CPR. In this work we utilize both S1 (total power) and CPR data from Mini-RF and CPR data from Arecibo to investigate the surface and subsurface rock content of the red spots and compare with the Diviner RA and H-parameter results.…”
Section: Circular Polarization Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…These inter-crater regions included both the rims and interiors of all craters smaller than 1 km, which our study and the work of Elder et al (2019) have shown can have significant rock abundance signals. The Vanga et al (2022) conclusion of an inverse relationship of rockiness with time for inter-crater regions may be the result of contamination by small craters like those we study and the evolution of rocks within the interior and rims of craters, which are known to enhance a rock abundance signal over time (Nypaver et al, 2021). We have identified and characterized more <1 km rocky craters than were available to Vanga et al (2022).…”
Section: Discussionmentioning
confidence: 73%